Karakteristik dan Perilaku Pencegahan Covid – 19 Pada Remaja di Kota Palangka Raya - Riyanti Riyanti; Saskia Nur Rahmadhani (Universitas Malahayati Lampung, 2022)
ABSTRACT: CHARACTERISTICS AND COVID-19 PREVENTION BEHAVIOR OF ADOLESCENTS IN THE CITY OF PALANGKA RAYA Introduction: Covid 19 can be experienced by anyone and affects all ages, including teenagers. The mortality rate is low in children and adolescents compared to adults but the risk of harm can still occur. Covid 19 occurs at the age of 5-14 years by 2.5% of cases, aged 15-24 years by 9.6% of cases in the world (WHO, 2020). In Indonesia, Covid-19 data at school age is 8.87% or 59,776 cases. Teenagers have a greater risk of contracting COVID-19 than younger children. Health protocols have been established to prevent the transmission of Covid 19, although there are still people including teenagers who tend not to follow the protocol. Purpose: To determine the effect of age, gender, and education on the behavior of preventing Covid 19 in adolescents in Palangka Raya City.Method: This type of research is descriptive-analytic with a Cross-Sectional approach. The population is teenagers aged 10-19 years who are in Palangka Raya City with a sample of 100 people. Sampling using a simple random sampling technique. Univariate analysis (frequency distribution) and bivariate analysis with chi-square.Results: 54% of respondents have good Covid-19 prevention behavior, 61% female gender, 49% age 15-17 years in the middle teenager category, and 51% secondary education. There is a significant relationship between age and Covid 19 prevention behavior (p-value = 0.043 OR 0.572), there is an influence of gender with Covid 19 prevention behavior (p-value = 0.007 OR 3.117), and there is an influence on the level of education on Covid 19 prevention behavior (p-value = 0.031 OR 0.873).Conclusion: The conclusions of this study illustrate that the characteristics of age, gender and level of education have an influence on the behavior of preventing Covid 19 in Palangka Raya City. Increasing age and increasing education have an impact on positive Covid 19 prevention behavior. Keywords: Characteristics, Behavior, Prevention of Covid 19, adolescents INTISARI: KARAKTERISTIK DAN PERILAKU PENCEGAHAN COVID – 19 PADA REMAJA DI KOTA PALANGKA RAYA Pendahuluan: Covid 19 dapat dialami siapa saja dan menyerang berbagai usia termasuk usia remaja. Tingkat kematian rendah pada usia anak dan remaja dibandingkan usia dewasa tetapi risiko bahaya tetap dapat terjadi. Covid 19 terjadi pada usia 5-14 tahun sebesar 2,5% kasus, usia 15-24 tahun sebesar 9,6% kasus di dunia (WHO, 2020). Di Indonesia data covid-19 pada usia sekolah sebesar 8,87% atau sebesar 59.776 kasus. Anak remaja memiliki risiko yang lebih besar untuk terkena Covid-19 dibandingkan anak yang berusia lebih kecil. Protokol kesehatan telah ditetapkan untuk mencegah penularan Covid 19, walaupun demikian masih ada masyarakat termasuk remaja yang cenderung tidak mengikuti protokol tersebut.Tujuan: untuk mengetahui pengaruh karakteristik umur, jenis kelamin dan pendidikan terhadap perilaku pencegahan Covid 19 pada remaja di Kota Palangka Raya.Metode Penelitian: Jenis penelitian deskriptif analitik dengan pendekatan Cross Sectional. Populasi adalah remaja berusia 10-19 tahun yang berada di Kota Palangka Raya dengan sampel berjumlah 100 orang. Pengambilan sampel menggunakan tehnik Simple random sampling. Analisis secara univariat (distribusi frekuensi) dan analisis bivariat dengan chi Square.Hasil: 54% responden berperilaku pencegahan Covid 19 baik, jenis kelamin perempuan 61%, usia 15-17 tahun kategori remaja tengah 49%, serta pendidikan menengah sebanyak 51%. Terdapat hubungan signifikan umur dengan perilaku pencegahan Covid 19 (p value=0,043 OR 0,572), ada pengaruh jenis kelamin dengan perilaku pencegahan Covid 19 (p value=0,007 OR 3,117), dan ada pengaruh tingkat pendidikan perilaku pencegahan Covid 19 (p value=0,031 OR 0,873).Kesimpulan: Simpulan penelitian ini menggambarkan karakteristik umur, jenis kelamin dan tingkat pendidikan remaja memiliki pengaruh terhadap perilaku pencegahan Covid 19 di Kota Palangka Raya. Semakin bertambah umur dan meningkat pendidikan berdampak pada perilaku pencegahan Covid 19 yang positif. Kata Kunci: Karakteristik, Perilaku, Pencegahan Covid 19, remaja